Evaluation of Mycobacterium indicus pranii as an immuno-potentiator in combination with 1’S-1’- acetoxychavicol acetate from the Malaysian Alpinia conchigera and cisplatin against various cancer types / Menaga Subramaniam - Menaga , Subramaniam (2017)
Cancer is a multistage disease consisting of tumour initiation, promotion and progression resulting from the modification of many genes. As a result, in many cases single drug treatment often fails to produce the desired therapeutic effect. In this study, a triple combinatorial usage between the immuno-potentiating activity of Mycobacterium indicus prani (MIP), the chemopotentiating properties of 1’S-1’-acetoxychavicol acetate (ACA) from the Malaysian Alpinia conchigera and the cytotoxic properties of the commercially available anti-cancer drug, cisplatin (CDDP) was proposed in order to synergistically chemosensitize and eradicate targeted malignancies in anti-cancer chemotherapeutic treatments in both in vitro and in vivo models. ACA is a phenylpropanoid which is isolated from the rhizomes of a sub-tropical ginger, Alpinia conchigera. MIP is a saprophytic bacterium which has been tested in a number of disease models and its immunomodulatory property in leprosy has been well documented. CDDP is a commercial anticancer agent clinically used for the treatment of various malignant tumours, such as head and neck, gastric, bladder, prostate, esophageal and osteosarcoma. In order to identify the potential cytotoxic element(s), a preliminary test was first carried out using four different fractions consisting of live bacteria, culture supernatant, heat killed bacteria and heat killed culture supernatant of MIP against human cancer cells A549 and CaSki by 3-(4,5-dimethyl thiazol)-2,5-diphenyl tetrazolium bromide (MTT) assay. Apoptosis was investigated in MCF-7 and ORL-115 cancer cells by poly-(ADP-ribose) polymerase (PARP) and DNA fragmentation assays. Among the four MIP fractions, only heat killed MIP fraction (HKB) showed significant cytotoxicity in various cancer cells with inhibitory concentration, IC50 in the range 5.6–35.0 μl/(1.0×106 MIP cells/ml). Evaluation on PARP assay further suggested that cytotoxicity in cancer cells were potentially induced via caspase-mediated apoptosis. The cytotoxic and apoptotic effects of MIP HKB have indicated that this fraction can be a good candidate to further identify effective anti-cancer agent. In addition, synergistic effects was identified in MCF-7 cells treated with double (MIP/ACA, MIP/CDDP) and triple (MIP/ACA/CDDP) combinations. The type of interaction between drugs/agent was evaluated based on combination index (CI) value being less than 0.8 for synergistic effect. Based on previous studies, mechanism of cell death upon drug combinations which involved intrinsic apoptosis and nuclear factor kappa-B (NF-κB) proteins was validated in western blot analysis. All double and triple combinations confirmed intrinsic apoptosis activation and NF-κB inactivation. Therefore, double and triple combination regimes which targets induction of the same death mechanism with reduced dosage of each drug, is proposed in this study. The in vitro combination effects were validated in in vivo animal model, BALB/c mice using 4T1 mice breast cancer cells. It was found that mice exposed to combined treatment displayed higher reduction in tumour volume compared to standalone drug. The immunohistochemistry and cytokine analysis provided evidence that combination chemotherapy not only downregulate NF-κB activation, but also reduced the expression of NF-κB regulated genes and inflammatory biomarkers. Consequently, combination therapy shows great therapeutic potential and a pioneer for the basis of future combination drug development.